Value-Based Decision Making for Redeveloping Transportation Facilities(Case Study: Kapit Airport) - Xin Xian, Beryl Wong (Universiti Teknologi PETRONAS, 2020)
Value based decision making is the consideration of cost and function in the decision to meet the stakeholders’ requirements. From the previous studies, there is lack of consideration on the criteria of value in decision making process. Hence, this research aims to identify the criteria for redeveloping transportation facilities based on function and cost. The ultimate goal of the research is to select the best valuable alternative for project redevelopment. An abandoned airport was chosen as the case study to evaluate the decision made by government to invest on the project of transforming the abandoned airport into a hospital which aims to cater the increasing demand for healthcare. Quantitative and qualitative approach has been applied through literature review, survey and interview to experts of transportation facilities development.